Contextual factors, methodological principles and teacher cognition - Walsh, Rupert; Wyatt, Mark (Studies in Second Language Learning and Teaching, 2014)
Teachers in various contexts worldwide are sometimes unfairly criticized for not putting teaching methods developed for the well-resourced classrooms of Western countries into practice. Factors such as the teachers’ “misconceptualizations” of “imported” methods, including Communicative Language Teaching (CLT), are often blamed, though the challenges imposed by “contextual demands,” such as large class sizes, are sometimes recognised. Meanwhile, there is sometimes an assumption that in the West there is a happy congruence between policy supportive of CLT or Task-Based Language Teaching, teacher education and supervision, and curriculum design with teachers’ cognitions and their practices. Our case study of three EFL teachers at a UK adult education college is motivated by a wish to question this assumption. Findings from observational and interview data suggest the practices of two teachers were largely consistent with their methodological principles, relating to stronger and weaker forms of CLT respectively, as well as to more general educational principles, such as a concern for learners; the supportive environment seemed to help. The third teacher appeared to put “difficult” contextual factors, for example, tests, ahead of methodological principles without, however, obviously benefiting. Implications highlight the important role of teacher cognition research in challenging cultural assumptions.